2014
DOI: 10.4103/0019-5049.147163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caudal clonidine on emergence agitation and postoperative analgesia after sevoflurane anaesthesia in children: Randomised comparison of two doses

Abstract: Background and Aims:Sevoflurane, a popular inhalational anaesthetic for children, has been associated with significant emergence agitation in the recovery phase. This study was intended to compare two doses of caudal clonidine added to ropivacaine 0.2% in order to decide on the optimal dose for prevention of sevoflurane induced emergence agitation (EA) and to get a meaningful prolongation of postoperative analgesia with minimal side effects.Methods:Sixty-one children aged 1–7 years (American Society of Anaesth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…reported clonidine as an effective caudal adjuvant with ropivacaine in a dose of two mcg/kg for prevention of EA. [ 2 ]Hence we used clonidine in a dose of 2 mcg/kg and preferred the caudal route of administration to give the patients the added benefit of better analgesic effect compared to intravenous route as was demonstrated in the study by Bock et al . [ 1 ]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…reported clonidine as an effective caudal adjuvant with ropivacaine in a dose of two mcg/kg for prevention of EA. [ 2 ]Hence we used clonidine in a dose of 2 mcg/kg and preferred the caudal route of administration to give the patients the added benefit of better analgesic effect compared to intravenous route as was demonstrated in the study by Bock et al . [ 1 ]…”
Section: Discussionmentioning
confidence: 99%
“…where they compared two different doses of clonidine- 1mcg/kg and 2mcg/kg given caudally with 0.2% ropivacaine and found that clonidine 2mcg/kg had lesser incidence of EA and also provided longer duration of analgesia. [ 2 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clonidine has been used at various doses caudally: 1–5 µg/kg. We chose a dose of 1 µg/kg as it is associated with longer duration of analgesia[ 26 27 ] and less postoperative emergence agitation. The dose of dexamethasone was chosen based on a study done earlier by Kim et al .…”
Section: Discussionmentioning
confidence: 99%